(untitled) (Research, Society and Development, 2022)
Surgical resections of maxillary tumors may cause bucosinusal communication that have as a rehabilitation method the manufacture of maxillary obturator prosthesis. Biomechanical aspects are the main challenge for effective prosthetic treatment. This article aims to report a rehabilitation case with maxillary obturator prosthesis after partial maxilectomy. A 14-year-old female patient sought dental care desiring to replace the provisional obturator prosthesis that had been made three years ago, to correct the maxillary defect generated by the surgical removal of an osteoma. After anamnesis, intra- and extra-oral examinations were chosen to perform a removable partial upper prosthesis with a palatine shutter. It was started by molding the two arcades to obtain the study models where the design and planning of the case was carried out. After mouth preparation and functional molding, the work model was obtained, used to make a metal frame that was proven and adjusted in the mouth analyzing the biomechanical aspects. After recording the facial arch and determining the intermaxillary relationships, the models were mounted on a semi-adjustable articulator, performed the selection and assembly of artificial teeth. Then, the aesthetic and functional test and necessary adjustments were performed. Subsequently, the molding of the closed mouth was performed, acrylization, polymerization, installation and proservations of the prosthesis were performed. The obturator prosthesis proved to be effective, in its biomechanical aspect, generating good retention and stability. The removable partial prosthesis is a favorable alternative to rehabilitation of patients undergoing maxillofacial mutilator surgeries.